2010
DOI: 10.1089/cap.2009.0065
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Psychotropic Medication Use over Time among Youth in Child Welfare/Child Protective Services

Abstract: Objective: The aim of this study was to examine rates of psychotropic medication use over time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
(23 reference statements)
2
26
1
Order By: Relevance
“…Although this finding occurred in the presence of adjustments for a binary measure of psychological distress, adolescents involved with CPS may have had more severe levels of distress that could not be captured by this measure. The finding of a greater likelihood of medication use is consistent with those of other studies indicating greater medication use among the CPS-involved (Leslie et al 2010;Zito et al 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although this finding occurred in the presence of adjustments for a binary measure of psychological distress, adolescents involved with CPS may have had more severe levels of distress that could not be captured by this measure. The finding of a greater likelihood of medication use is consistent with those of other studies indicating greater medication use among the CPS-involved (Leslie et al 2010;Zito et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Research on mental health service utilization among CPS-involved youth, however, often does not consider the use of prescription medications. The limited number of existing studies tends to focus on children within foster care (Ferguson et al 2006;McMillen et al 2004;Zima et al 1999;Zito et al 2008) or within the child welfare system generally (Leslie et al 2010;Raghavan et al 2005), with various age ranges that limit knowledge of medication use and its correlates among adolescents with histories of family involvement with CPS. Knowledge about age groups is particularly limited when studies group children and adolescents together (e.g., Raghavan et al 2005;Zito et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No randomised trials were found. Cohorts included the National Survey of Child and Adolescent Wellbeing (NSCAW, Berger et al ., 2009; Casanueva et al ., ; Cheng and Lo, ; Hurlburt et al ., ; Kolko et al ., ; Leslie et al ., , ; Raghavan et al ., ; Ringeisen et al ., ; Stacks et al ., ; Stahmer et al ., ; Traube et al ., ; Wall and Kohl, ) and the NSCAW‐II (Font and Maguire‐Jack, ; Fowler et al ., ; Horwitz et al ., ), a data‐set developed by Widom (DeGue and Spatz Widom, ; McMahon and Clay‐Warner, ; Widom, ), Swedish registry data (Berlin et al ., ; Vinnerljung et al ., , ), Runyan and Gould's (, ) historical cohort, a cohort used by Mennen et al . () and Negriff et al .…”
Section: Resultsmentioning
confidence: 98%
“…About 1 in 7 children in foster care receives a psychotropic drug at a given point in time (Zima, Bussing, Yang, & Belin, 2000), a rate that rises to nearly 1 in 4 when these children are followed over time (Leslie, Raghavan, Zhang, & Aarons, 2010). Approximately 40% of children in foster care reportedly received multiple psychotropic medications simultaneously (J.…”
Section: Introductionmentioning
confidence: 99%